Description of a New Simple and Cost-Effective Molecular Testing That Could Simplify MUC1 Variant Detection - Victor Fages; Florentin Bourre; Romain Larrue; Andrea Wenzel; Jean-Baptiste Gibier; Fabrice Bonte; Claire-Marie Dhaenens; Kendrah Kidd; Stanislav Kmoch; Anthony Bleyer; François Glowacki; Olivier Grunewald (Kidney International Reports)
Introduction: Patients with autosomal dominant tubulointerstitial kidney disease (ADTKD) usually present with nonspecific progressive chronic kidney disease (CKD) with mild to negative proteinuria and a family history. ADTKD-MUC1 leads to the formation of a frameshift protein that accumulates in the cytoplasm, leading to tubulointerstitial damage. ADTKD-MUC1 prevalence remains unclear because MUC1 variants are not routinely detected by standard next-generation sequencing (NGS) techniques. Methods: We developed a bioinformatic counting script that can detect specific genetic sequences and count the number of occurrences. We used DNA samples from 27 patients for validation, 11 of them were patients from the Lille University Hospital in France and 16 were from the Wake Forest Hospital, NC. All patients from Lille were tested with an NGS gene panel with our script and all patients from Wake Forest Hospital were tested with the snapshot reference technique. Between January 2018 and February 2023, we collected data on all patients diagnosed with MUC1 variants with this script. Results: A total of 27 samples were tested anonymously by the BROAD Institute reference technique for confirmation and we were able to get a 100% concordance for MUC1 diagnosis. Clinico-biologic characteristics in our cohort were similar to those previously described in ADTKD-MUC1. Conclusion: We describe a new simple and cost-effective method for molecular testing of ADTKD-MUC1. Genetic analyses in our cohort suggest that MUC1 might be the first cause of ADTKD. Increasing the availability of MUC1 diagnosis tools will contribute to a better understanding of the disease and to the development of specific treatments.